Extracellular cyclophilin A induces cardiac hypertrophy via the ERK/p47phox pathway. (1st December 2020) - Cao, Mengfei; Mao, Ziqi; Peng, Meiling; Zhao, Qianru; Sun, Xia; Yan, Jinchuan; Yuan, Wei
Abstract: Excessive reactive oxygen species (ROS) are a critical driver of cardiac hypertrophy developing into heart failure. Cyclophilin A (CyPA), a member of the cyclophilin family, has been highlighted as a main secreted ROS-induced factor. The mechanism by which extracellular CyPA interacts with cardiomyocytes is unclear. We showed that extracellular CyPA is upregulated in cardiac hypertrophy rats and expressed around hypertrophic cardiomyocytes. Cell experiments further confirmed that extracellular CyPA induces H9c2 cardiomyocytes hypertrophy via ROS generation. Extracellular CyPA-induced ROS is derived from nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase, and extracellular CyPA activates p47phox membrane translocation through ERK1/2 pathway. When blocking extracellular matrix metalloproteinase inducer (EMMPRIN), most of the extracellular CyPA effects were significantly inhibited. The current study shows that extracellular CyPA is one of the key factors linking oxidative stress and cardiac hypertrophy, and may be a potential target for cardiac hypertrophy therapy. Highlights: Extracellular Cyclophilin A directly induces cardiac hypertrophy. Extracellular Cyclophilin A activates NADPH oxidases in a way that is different from intracellular CyPA. Extracellular Cyclophilin A mediates intracellular signaling pathways by binding to its receptor.